A model for enhancing creativity, collaboration and pre‑professional identities in technology‑supported cross‑organizational communities of practice - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando (My University, 2023)
This research proposes that technology-supported cross-organizational (universityindustry) Communities of Practice (CoPs), which are integrated into the Design Studies curriculum in Higher Education, can foster robust university-industry collaborations. These can help bridge the reported gap between the actual versus the expected soft skills and personae of young graduates transitioning to the creative industries today. CoPs are groups of people who share a common interest in an area of ‘endeavor’ and connect to co-create competence in that area through their practice. This paper makes two overarching research contributions. First, it informs about the design, enactment, and evaluation of a student CoP in an undergraduate Design course which was expanded to include members from the industry as clients, alumni mentors, and expert evaluators. Drawing from rich empirical data, the paper explains the designed and emergent learning phenomena of CoP participation and its effects on the students’ creative and socio-epistemic outcomes, as well as their pre-professional identities. Second, it presents a governance model with three sets of actionable guidelines, namely the Set (technology), the Social (collaborative), and the Epistemic (learning) components. The entire body of work validates the critical interlocking of these components to form a robust social learning model that appropriates the complex practices of cross-organizational CoPs in Higher Education Design studies.
Keywords: Communities of practice; Technology configuration; HCI; Creativity; Collaboration; Authenticity; Pre-professional identity; Governance model